Composition and similarity of vegetation types in the Mount Seulawah Agam geothermal area, Aceh Besar District - DAHLAN DAHLAN; MUHAMMAD DOUDI; SAIDA RASNOVI; DALIL SUTEKAD; MUSLICH HIDAYAT (Jurnal Natural, 2023)
The Mount Seulawah Agam area is an active volcanic area that has an impact on the emergence of symptoms of volcanism. Such environmental conditions will cause the vegetation that grows in the area to be unique and not commonly found in other areas. Apart from that, the area is still relatively natural and has not experienced much disturbance by human activities. This study aims to determine the composition and similarity of vegetation types in the geothermal area of Mount Seulawah Agam, Aceh Besar District. Data collection in the field was carried out using the multiple square method which was placed in a stratified sampling based on the specified soil temperature zone. Each zone was laid out in 4 square plots in a systematic random manner. Each plant contained in the observation plot is recorded in the name of the plant species using a flora identification book, and the number of individuals of each type is recorded. Data analysis was carried out using the Important Value Index analysis, and the Sorenson Similarity Index. The results showed that there were 65 species from 611 individual plants identified starting from the growth rate of seedlings, sapling, poles, and trees. The similarity index of plant species at each growth stage in the Seulawah Agam geothermal area, Aceh Besar District generally has different species similarity in each observation zone, that is, the average is below 50%. This condition indicates that there are significant differences in plant structure at various growth rates in each zone